Analysis of Risk Factors for the Incident of Hypertension in Participants of the Chronic Disease Management Program (PROLANIS) - Lestari, Gianita Yulia; Alami, Pernix Cantika; Gunadi, Helmi Rosa (GLOBAL HEALTH SCIENCE GROUP, 2024)
Hypertension is a non-communicable disease that often appears without symptoms. It is said to be hypertension if blood pressure is ≥ 140/90 mmHg. Objective: This study aims to determine the factors that contribute to the incidence of hypertension in prolanis participants in the Sindangkerta health center working area, Cianjur Regency. The method in this research is quantitative research using a cross-sectional approach. The population in this study were all prolanis participants at the Sindangkerta Community Health Center, Cianjur Regency. Data collection in this study used primary data through questionnaires and secondary data through data on prolanis participants in the Sindangkerta health center working area, Cianjur Regency, identity card, data on diagnosed hypertension and HbA1c examination data on prolanis patients. Data analysis used the chi-square test with a degree of significance (α) = 0.05. The results showed that there was a significant relationship between the variables age (p = 0.011), gender (p = 0.001), family history of hypertension (p = 0.015), nutritional status (BMI) (p = <0.001), smoking history ( p = 0.039), physical activity (p = 0.015), history of alcohol consumption (p = 0.010), high salt diet (p = 0.022) and history of diabetes mellitus (p = 0.001) with the incidence of hypertension in chronic disease management program participants (prolanis) in the working area of the Sindangkerta Community Health Center, Cianjur Regency.